EFFECTIVENESS OF DA’WAH THROUGH INSTAGRAM FOR STUDENTS AT MADRASAH ALIYAH KARYA MADANI, WEST BANDUNG REGENCY - Yusuf, Yogi Muhammad; Fitrananda, Charisma; Iqbal, Mochamad (LPM Universitas Pasundan, 2025)
This community service program aims to empower students of Madrasah Aliyah Karya Madani in West Bandung Regency through training on enhancing the effectiveness of Islamic da’wah using Instagram. The background of this program is the students’ lack of knowledge and skills regarding the profession of content creators, especially in producing positive and creative da’wah content on social media. The method applied included contextual approach, consisting of education on digital literacy, workshops on content creation, simulation of da’wah content production, and mentoring to ensure sustainable practice. The results showed that students gained awareness of the positive impact of becoming da’wah content creators, improved their technical skills in producing Instagram content, and successfully created content that highlighted local and religious values. This activity has contributed to the development of students’ creativity, digital literacy, and opportunities in the creative economy sector.